The interrelationships of birthweight, inflammation and body composition in healthy adults. (3rd March 2016) - Kofler, Thomas; Bossard, Matthias; Aeschbacher, Stefanie; Tabord, Alexandra; Ruperti Repilado, Francisco Javier; van der Lely, Stéphanie; Berger, Sebastian; Risch, Martin; Risch, Lorenz; Conen, David
Abstract: Background: Lower birthweight is associated with an increased risk of cardiovascular diseases and diabetes. We hypothesized that inflammation and body fat may be potential mediators for these inverse relationships. Materials and methods: Healthy adults aged 25–41 years were enrolled in a prospective population‐based cohort study in the Principality of Liechtenstein. Main exclusion criteria were diabetes, overt cardiovascular disease or a body mass index > 35 kg/m 2 . Birthweight was self‐reported by the study participants. White blood cell (WBC) count and high‐sensitivity C‐reactive protein (hs‐CRP) levels were assayed from fresh blood samples. Body composition was determined by bioelectrical impedance analysis. Multivariable linear regression models were constructed to assess the relationships between birthweight, inflammation and body composition. Results: Our sample consisted of 1774 participants (53·4% females) with a median age of 37 years. Median birthweight was 3355 g. In multivariable models, we found an inverse relationship of birthweight with hs‐CRP levels (β −0·010 (95% CI −0·02; −0·002), P = 0·01) and WBC count (β −0·002 (95% CI −0·004; −0·0002), P = 0·03). Additional adjustment for body fat mass attenuated these relationships (β −0·008 (95% CI −0·02; 0·0003), P = 0·06 for hs‐CRP levels and (β −0·002 (95% CI −0·004; 0·0006), P = 0·16 for WBC count. Body fat mass itself was strongly associated with birthweight (β −0·06 (95% CI −0·10; −0·03), P < 0·0001). Conclusion: Birthweight is inversely associated with inflammation in adulthood. This relationship may be mediated by an elevated body fat mass among individuals with lower birthweight.